Effects of Puff Adder Venom on the Coagulation Mechanism - Phillips, Louise L.; Weiss, H. J; Christy, N. P (Thrombosis and Haemostasis, 1973)
Studies of the in vitro effects of puff adder venom (Bitis arietans) on the coagulation system of human plasma have suggested this venom activates factor XI. Incubation with the venom results in a prolongation of the partial thromboplastin times in glass which is associated with a depletion of factors V, VIII, and fibrinogen. The latter may be due to the proteolytic properties of the venom. Soluble fibrin monomer complexes are formed rapidly after addition of the venom to normal plasma. The venom also causes platelet aggregation which is not inhibited by heparin.